BAHAN AJAR FISIKA ONLINE UNTUK MENGEMBANGKAN KEMANDIRIAN DAN MINAT BELAJAR SISWA PADA POKOK BAHASAN KALOR (UPEJ Unnes Physics Education Journal, 2013)
This research is aimed to determine the development of independence and student interest after using online physics teaching materials on the subject of heat in SMP N 2 Semarang. The research is the development of test design using One-Group Pretest-Posttesst Design, which is part of the Quasi-Experimental Design. Sampling with purposive sampling technique that is class VII B. Methods of data collection in this research is a method of documentation, testing, and questionnaires. Before research implemented online physics teaching materials validated by expert lecturers. Online physics teaching materials tested on 10 respondents then applied to the classroom. The results of t-test and gain analysis indicate that there was development on the independence and student interest but not signifkan and stil low. Based on this results concluded that the online physics teaching materials can develop independence and student interest in the subject of heat. However, the results is not significant and low.